2003
DOI: 10.1046/j.1460-9592.2003.t01-1-00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Rapid Rhythms Recorded Within Pulmonary Veins During Atrial Fibrillation

Abstract: Rapid rhythms often arise in the pulmonary veins during atrial fibrillation (AF). The activation patterns within pulmonary veins during these rapid rhythms are not well described. In 39 patients with paroxysmal AF, ostial recordings were obtained during AF in 110 pulmonary veins with a decapolar distal ring catheter. Pulmonary vein tachycardia (PVT) was defined as a pulmonary vein (PV) rhythm that had a cycle length shorter than at the adjacent left atrium. During AF, PVT was recorded in 93% of PV's, usually i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…A recent study by Kalifa and colleagues 18 also described evidence of sustained reentry at the LA-PV junction in the sheep model during periods of increased intra-atrial pressure. Although Tada and colleagues 8 found evidence of repetitive firing from the PVs during ongoing AF, Ndrepepa and colleagues, 19 using basket mapping of the LA, found that the posterior LA, not the PVs, was the driver of AF in these patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent study by Kalifa and colleagues 18 also described evidence of sustained reentry at the LA-PV junction in the sheep model during periods of increased intra-atrial pressure. Although Tada and colleagues 8 found evidence of repetitive firing from the PVs during ongoing AF, Ndrepepa and colleagues, 19 using basket mapping of the LA, found that the posterior LA, not the PVs, was the driver of AF in these patients.…”
Section: Discussionmentioning
confidence: 92%
“…Others have reported focal firing within the PVs during sustained AF. 8 However, the role of the left atrium (LA) and PVs in the maintenance of sustained AF in humans is still emerging.…”
mentioning
confidence: 99%
“…Although persistent, rapidly firing foci from the pulmonary veins have been demonstrated to be present during AF [45] more recent studies have found conclusive evidence that drivers of AF behave like reentrant circuits rather than as foci at least in paroxysmal cases [46]. …”
Section: Implications Of Df Analysis In Afmentioning
confidence: 99%
“…An arrhythmogenic PV was defined as a PV in which a PAC triggering AF was identified during SR 11,12 and/or as a PV demonstrating PV tachycardia during AF. 22 Segmental isolation was attempted in each of the 3 patients as previously described. [10][11][12][13][14][15][16] A 7Fr decapolar ring catheter (Lasso, Biosense Webster, Diamond Bar, CA, USA) and a 7Fr quadripolar ablation catheter with a 4-mm distal electrode, embedded thermistor, 2-5-2 mm inter-electrode spacing, and a deflectable tip (Biosense Webster) were inserted into the left atrium.…”
Section: Electrophysiologic Study and Rcamentioning
confidence: 99%